Analysis of Employee Performance at UPT Asrama Haji Makassar: The Role of Human Resource Development, Compensation, Work Environment, Leadership, and Work Motivation - Rosmawati, Rosmawati; Megawaty, Megawaty; Nurdin, Maryam (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
This study aims to analyze employee performance at the Makassar Hajj Dormitory UPT by focusing on the factors of human resource (HR) development, compensation, work environment, leadership, and work motivation. A quantitative research approach was employed through a survey of all employees at UPT Asrama Haji Makassar. The sampling technique used a saturated sample with 147 respondents. Data were collected using questionnaires and analyzed through instrument testing, classical assumption tests, multiple linear regression, and hypothesis testing. The findings reveal that HR development, work environment, and leadership have a positive and significant influence on both employee motivation and performance, while compensation has a negative and significant effect. Furthermore, work motivation shows a negative influence on employee performance. The results also indicate that HR development, compensation, work environment, and leadership affect employee performance indirectly through work motivation as a mediating variable. This study emphasizes the importance of HR development strategies, supportive work environments, and effective leadership in improving employee performance at UPT Asrama Haji Makassar. Conversely, inappropriate compensation systems tend to reduce employee motivation and performance.